2022
DOI: 10.1016/j.cbpra.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mental Health Interventions for Depression

Abstract: This paper provides an overview of the of digital mental health (DMHI) interventions for depression. The paper begins with a description of the clinical context and services needs for persons experiencing depressed mood. It is well-known that there is a large gap between the availability of evidence-supported psychotherapy for depression and the large number of people who would likely benefit from it. DHMIs based on a cognitive-behavioral (CBT) model have shown substantial promise as a method to deliver tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…While advances in technology have a major potential to improve the accessibility of psychosocial interventions for all cancer survivors, including AYAs, investigators should carefully consider other key aspects of technology-assisted treatment development, namely treatment fidelity and treatments' interactivity and engagingness for AYAs. 50 Investigators of technology-assisted interventions for AYA cancer survivors should adopt an interdisciplinary approach in developing technology-assisted platforms to improve interactivity and engagement, employing psycho-oncologists, computer scientists, media specialists, developmental psychologists, game designers, and specialists in other relevant disciplines. It is also essential for researchers and clinicians to incorporate the social determinants of health and health disparities in designing technology interventions supporting AYAs, given the unique transition-of-care challenges that are common among this population.…”
Section: Discussionmentioning
confidence: 99%
“…While advances in technology have a major potential to improve the accessibility of psychosocial interventions for all cancer survivors, including AYAs, investigators should carefully consider other key aspects of technology-assisted treatment development, namely treatment fidelity and treatments' interactivity and engagingness for AYAs. 50 Investigators of technology-assisted interventions for AYA cancer survivors should adopt an interdisciplinary approach in developing technology-assisted platforms to improve interactivity and engagement, employing psycho-oncologists, computer scientists, media specialists, developmental psychologists, game designers, and specialists in other relevant disciplines. It is also essential for researchers and clinicians to incorporate the social determinants of health and health disparities in designing technology interventions supporting AYAs, given the unique transition-of-care challenges that are common among this population.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that smartphone-based interventions are effective in reducing depressive symptoms ( g = 0.26–0.41) (Kerst et al, 2020; Linardon et al, 2019; Weisel et al, 2019). However, high dropout rates remain a major challenge in their implementation (Himle et al, 2021; Torous et al, 2020; Webelhorst et al, 2020). For example, a recent meta-analytic review of randomized controlled trials (RCTs) found that the pooled dropout rate in smartphone-based interventions that specifically targeted depressive symptoms was 26.2% (Torous et al, 2020), and this figure increased to 48% after adjusting for publication bias.…”
mentioning
confidence: 99%
“…More intuitive and less academically oriented while focusing on central concepts. For more information about Entertain Me Well see: Weaver et al, 2021[ 91 ], Himle et al, 2021 [ 92 ].…”
Section: Methodsmentioning
confidence: 99%